Work weaknesses and potentials: perception of mobile emergency service nurses - Anelise Bertolino Pereira; Júlia Trevisan Martins; Renata Perfeito Ribeiro; Maria José Quina Galdino; Lígia Carreira; Marcia Eiko Karino; Patrícia Aroni (Associação Brasileira de Enfermagem, 2020)
ABSTRACT Objectives: to know nurses' perceptions about their work process in a Mobile Emergency Care Service. Methods: qualitative study conducted with 12 nurses whose speeches were submitted to Content Analysis. Results: there are weaknesses related to overload of activities, numerous functions, indirect supervision, risk situations, difficulties in relationship with hospitals, lack of vehicles and professionals, inappropriate places to provide care and lack of knowledge of the population about urgent and emergency care. Potentials were associated with effective interpersonal relationships, continuing training, security when arriving at the place of care, care protocol and taste for what you do. Final Considerations: the identified weaknesses need to be noted by managers and nurses. Thus, they would seek to establish actions to diminish them and maximize potentials, which could improve patient care as well as reduce occupational risks and, in turn, promote workers' well-being.